A study on notifiable diseases reported in a tertiary care hospital - Asaithambi, Anupriya; Alagappan, Uma; Ragavendran, Susethira; Ganesan, Vazhavandal; ., Saraswathi; ., Lalithambigai; Edwin, Diego (International Journal Of Community Medicine And Public Health, 2017)
Background: This study was undertaken to analyse the various diseases reported in a teritary care hospital. To find out the most common disease notified. Methods: This is hospital record based retrospective study. The data was collected from notifiable disease register maintained in the Department of Microbiology and also from medical records section of this hospital from August 2013 to December 2016. Results: The total number of cases reported was 1613. Of the 22 diseases listed by the government only seven were more common. Tuberculosis ranks the top followed by HIV-AIDS, malaria, dengue respectively. The disease group commonly affected is 13-59 years (61.5%) with male (63.5%) predominance. Conclusions: To prevent the spread of epidemic, the health care personnel must be adequately trained to identify the disease and notify the higher authorities.